English language education on-line game and brain connectivity. Issue 1 (29th September 2016) - Hong, Ji Sun; Han, Doug Hyun; Kim, Young In; Bae, Su Jin; Kim, Sun Mi; Renshaw, Perry
Abstract: The HoDoo English game was developed to take advantage of the benefits attributed to on-line games while teaching English to native Korean speakers. We expected to see that the improvements in the subjects' English language abilities after playing the HoDoo English game would be associated with increased brain functional connectivity in the areas of the brain involved in the language production (Broca's area) and the understanding (Wernicke's area) networks. Twelve children, aged nine and ten, were asked to play the on-line English education game for 50 minutes per day, five days per week for twelve weeks. At baseline, and again at the end of twelve weeks of game play, each child's English language ability was assessed and a functional magnetic resonance imaging (fMRI) scan was conducted. The on-line English education game play effectively improved English language skills, especially in terms of non-verbal pragmatic skills. Following twelve weeks of on-line English education game play, the children showed positive connectivity between Broca's area and the left frontal cortex as well as between Wernicke's area and the left parahippocampal gyrus and the right medial frontal gyrus. Changes in pragmatic scores were positively correlated with average peak brain activity in the left parahippocampal gyrus. To the best of our knowledge, this is the first study to report an improvement in English ability and changes in brain activity within language areas after on-line language education game play.